2020
DOI: 10.5194/aab-63-293-2020
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality of Pulawska breed pigs and image of longissimus lumborum muscle microstructure compared to commercial DanBred and Naima hybrids

Abstract: Abstract. The objective of this article was the evaluation of selected properties of meat quality including the characteristics of longissimus lumborum (LL) muscle microstructure of Pulawska breed pigs and fatteners of the DanBred and Naima hybrids which are used in national meat production. Three genetic groups of fatteners were studied in the experiment: group I – DanBred hybrid; group II – Naima hybrid; and group III – the Pulawska breed. Pig fattening took place under the same environmental conditions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 36 publications
3
20
3
2
Order By: Relevance
“…However, for example, Parunović et al [41] found higher cholesterol content (by 15.8%) in the meat of Mangalitsa than in the meat of Swedish Landrace. Our observations did not prove an effect of genotype on muscle fiber diameter, however, it is evident that muscle fibers in the meat of CH pigs are stronger, which is related to a higher lean meat content [42]. In the present study, meat oxidation was affected by genotype on Day 3 and Day 6 after the slaughter.…”
Section: Physical and Chemical Characteristics Of Musculus Longissimus Lumborum Et Thoraciscontrasting
confidence: 90%
“…However, for example, Parunović et al [41] found higher cholesterol content (by 15.8%) in the meat of Mangalitsa than in the meat of Swedish Landrace. Our observations did not prove an effect of genotype on muscle fiber diameter, however, it is evident that muscle fibers in the meat of CH pigs are stronger, which is related to a higher lean meat content [42]. In the present study, meat oxidation was affected by genotype on Day 3 and Day 6 after the slaughter.…”
Section: Physical and Chemical Characteristics Of Musculus Longissimus Lumborum Et Thoraciscontrasting
confidence: 90%
“…Muscle acidification 45 min after slaughter (pH 1 ) and ultimate acidification (pH u ) are key factors that determine the quality of pork [2,[9][10][11][12]. Muscle pH measurements 45 min after slaughter (pH 1 ) are used to predict meat quality and its classification in respect to PSE (pale, soft, exudative), normal, and DFD (dark, firm, dry) types [13].…”
Section: Introductionmentioning
confidence: 99%
“…The values of meat acidification measured 45 min after slaughter lower than 5.8 as typical of PSE meat, values from 5.8 to 6.0 as characteristic of semi-PSE meat, and values above 6.0 as characteristic of normal meat. Limit values of pH 1 measurements are used by most researchers as meat quality classification criteria [8,10,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Pork accounts for nearly 40% of the global production and consumption of meat [ 1 ]. It is a source of complete protein and significant amounts of easily assimilated iron, zinc, selenium, copper, and vitamins from the B group, as well as bioactive compounds [ 2 , 3 , 4 ]. The content of fat and its fatty acid profile are nutritionally essential [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%